Perlindungan Hukum Pemegang Hak Milik Atas Tanah Wakaf - Yeni Indrayani Oktaviana (Jatiswara, 2017)
This research was conducted to find out how the legal arrangement of the right holder of land ownership of waqf land and how is the legal protection mechanism of the holder of property rights on wakaf land. This research is a normative research with legal, conceptual and historical approach. The results showed that the form of protection against the owners of land ownership of wakaf land is by registering and administrating at the appointed institution namely the Ministry of Agrarian Affairs and Spatial / National Land Agency after the pledge of waqf and the issuance of wakaf certificate based on a decree granting rights to the land of endowments Derived from customary land and from state land and issued a wakaf certificate on behalf of the landowners of wakaf by firstly listing on the land book. The recording is done because wakaf is not enough with verbal only, if only done with oral then wakaf becomes invalid.